RESEARCH OF DEVELOPMENT AND SUPPORT PROCESSES OF SMALL BUSINESS IN UKRAINE AND POLAND (Regional aspects of productive forces development of Ukraine, 2019)
The article provides a theoretical generalization of the processes of development and support of small business at the state level. The article analyzes the current state of small business in Ukraine, the international image of the country and its place in the international business environment. The features of the state policy of supporting the development of small business in Ukraine and Poland are revealed and a positive experience that can be implemented in Ukraine is highlighted. In particular, it is  determined that due to small firms a competitive environment is formed that positively affects the market conditions, provides  economic growth, and also affects the processes of employment of the population. The experience of the state policy of supporting the development of small business is considered, and it is  determined that support for the development  of small enterprises in the economies of the developed countries is ensured by systematic comprehensive support from the state, which is supported by regular and significant in its volume of budget financing. In addition, the main directions are determined the state strategy for small business development in Western European countries, in particular Poland.